Design of network management and regulation system over flexible reconfiguration - Yu-feng LI; Han QIU; Qin-rang LIU; Ju-long LAN (Tongxin xuebao)
Network management and regulation system is a new arising appliance for the manageable,controllable and trustworthy demand of the Internet.The architecture design of the backbone link-level management and regulation system usually follows the core router,in which the separation of the data plane and the control plane could not meet the requirement of HW/SW data co-process,the rigid connection with closed building style could not satisfy the flexible identification of new applications.The loosely coupled switching HW/SW co-process architecture and the iterative looping HW/SW migration architecture were proposed,which could satisfy the above HW/SW co-process demand and the new application flexible identification demand.